2007
DOI: 10.1371/journal.pone.0000182
|View full text |Cite
|
Sign up to set email alerts
|

Vector-Virus Mutualism Accelerates Population Increase of an Invasive Whitefly

Abstract: The relationships between plant viruses, their herbivore vectors and host plants can be beneficial, neutral, or antagonistic, depending on the species involved. This variation in relationships may affect the process of biological invasion and the displacement of indigenous species by invaders when the invasive and indigenous organisms occur with niche overlap but differ in the interactions. The notorious invasive B biotype of the whitefly complex Bemisia tabaci entered China in the late 1990s and is now the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
317
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 276 publications
(332 citation statements)
references
References 48 publications
9
317
0
6
Order By: Relevance
“…The results of Jiu et al (2007), Kempema et al (2007), and Zarate et al (2007) suggest that the increased aggregation of whitefly on TYLCCNV-infected plants may be due to possible suppression by the virus of specific JAresponsive plant genes that have defense function against the vector. Our results on the ability of ␤C1 to suppress expression of selective JA-responsive genes are consistent with this hypothesis.…”
Section: Selective Repression Of Ja-responsive Genes By ␤C1mentioning
confidence: 96%
See 2 more Smart Citations
“…The results of Jiu et al (2007), Kempema et al (2007), and Zarate et al (2007) suggest that the increased aggregation of whitefly on TYLCCNV-infected plants may be due to possible suppression by the virus of specific JAresponsive plant genes that have defense function against the vector. Our results on the ability of ␤C1 to suppress expression of selective JA-responsive genes are consistent with this hypothesis.…”
Section: Selective Repression Of Ja-responsive Genes By ␤C1mentioning
confidence: 96%
“…Infections by TYLCCNV and TbCSV carrying satellite DNA␤ are not only associated with disease symptoms but also known to promote population increase of its vector, the type B invasive whitefly (Jiu et al 2007). Although the mutualism between the two gemini viruses and whitefly has been shown to be indirect via the host plants, the precise mechanism remains to be elucidated.…”
Section: Selective Repression Of Ja-responsive Genes By ␤C1mentioning
confidence: 99%
See 1 more Smart Citation
“…Crops will foster viruses with particular ecological lifestyles. Crops provide vectors with a predictable succession of suitable herbaceous hosts on which they can reproduce rapidly and produce very large migrant populations, and virus infections often aid vector infestations and virus spread (Baker, 1960;Jiu et al, 2007). Thus, since the mid-Holocene, agriculture may have fostered the emergence, spread and dominance of virus taxa with particular ecologies suited to life in the continuously disturbed environments provided by humans.…”
Section: Viral Origins Evolution and The Invention Of Agriculturementioning
confidence: 99%
“…Also, viruses may affect the population dynamics of then insect vector. For instance, it has been shown that virus infection aas an influence on both the attraction of insect vectors by host plants and on thenreproductive potential (Fereres et al 1999;Jiu et al 2007). Interestingly, the effect of virus infection on aphid biology may depend on the transmission manner, nonpersistent or persistent (Eigenbrode et al 2002), Research on virus-vector interactions presently lags behind that on virus-host interactions.…”
Section: Recent Times: New Concepts and New Challengesmentioning
confidence: 99%